De la instrucción a la literalización - Ulloa Brenes, Gilbert (2009)
In this paper about Psychology of Education, I propose to distinguish the educational work centered in the instruction-evaluation relationship, which, following the structuralist Barthes, I’m understanding as an education based on critical truthfulness, from an educational work trying to recover all language possibilities, understood as literalization, that is, the appropriation by the educational subjects of a logos that the educational instruction-evaluation has robbed them of..